Analisis Strategi dan Kinerja Aparatur Inspektorat dalam Pengawasan Keuangan Daerah - Mainita Mainita; Ahmad Soleh; Arman Syafaat (Universitas Batanghari, 2022)
This study aims to recognize: analyzing the performance of the Inspectorate in Jambi City; analyze the influence of continuing education, independence, motivation and organizational commitment to the performance of the Inspectorate apparatus, and analyze strategies to increase the supervision of the Inspectorate in realizing good governance. This research uses descriptive, qualitative, and quantitative analysis. with the reseach library approach. The study used primary data and secondary data. Primary data is obtained through questionnaires or interviews directly to respondents using the linkert scale on the apparatus that participates in regular examinations in the Jambi City Inspectorate with a purposive sampling approach. The data analysis tools used in this investigation are interactive trigulation models for performance problems, multiple regressions for second problems and swot analysis for third problems. The results of the analysis showed that the performance of the inspectorate in Jambi City was good, then simultaneously continuing education, independence, motivation and commitment of the organization of positive influence on the performance of the Jambi City Inspectorate apparatus. While the factors that partially affect the performance of the Jambi City Inspectorate apparatus are independence and motivation. For the variables of continuing education and organizational commitment partially have no effect on the performance of the Jambi City Inspectorate apparatus.